Euzophera Punicaella Mooze (Lepidoptera) bioecology and development of host entomophagic equilibrium in biocenosis - Kimsanboev Khujamurod; Rustamov Atkham; Jumaev Rasul; Usmonov Mukhriddin (E3S Web of Conferences, 2021)
Pomegranate (Punica granatum L.) is grown in tropical and subtropical regions of the world. Pomegranate has been grown in Central Asia for almost 2,000 years. More than 25% of pomegranates in Central Asia are located in Uzbekistan. Pomegranate fruit pest (Euzophera punicaella Mooze) is one of the main pests that reduce the basic quality and export yield of pomegranate. When chemical control measures are applied against them, pomegranates lose their quality and export character and do not always give the expected results. The larvae develop inside the fruit, which is why the effectiveness of medicines is low. We used entomophagous biological agents against this pest, such as Trichogram pintoi, Trichogram chilonis, Trichogram evanescens, Trichogram dendrolimi, and Trichogram ostrinae. For pomegranate fruit worms, Bracon hebetor Say entomophagy was highly effective when used in the laboratory in a ratio of 1:10. It is obvious that biological control measures provide high quality and high efficiency.